On the Relation between Dual-Rate Discounting and Substitutability - Tomas Kögel (Kiel Institute for the World Economy (IfW), 2009)
To justify substantial emission reductions, recent literature on cost-benefit analysis of climate change suggests discounting environment consumption with an environmental discount rate instead of a consumption discount rate that is usually used in cost-benefit analysis. The present study clarifies that whether or not this dual-rate discounting approach succeeds in justifying substantial emission reductions depends on whether or not environment and goods consumption are substitutes in the Hicks-Allen sense and in the Edgeworth-Pareto sense (substitutes in the Hicks-Allen sense implies the Hicksian goods demand to be increasing in the relative price of environmental goods, while substitutes in the Edgeworth-Pareto sense implies the marginal utility of goods consumption to be decreasing in environment consumption). Moreover, a low intratemporal elasticity of substitution between environment and goods consumption within a period contributes to a low environmental discount rate in comparison to the consumption discount rate, while a low intertemporal elasticity of substitution between composite consumption of different periods contributes to declining discount rates over time.
Keywords: Q28; H43; D90; 330; Discounting; dual-rate discounting; environmental discount rate; cost-benefit analysis; climate change; Klimaschutz; Kosten-Nutzen-Analyse; Umweltökonomik; Soziale Diskontrate; Theorie